HUBUNGAN PERMAINAN LEGO DENGAN KONSENTRASI BELAJAR ANAK AUTIS DI SEKOLAH LUAR BIASA - Dhian Regi Samarta Durin; M. Shodiq A.M; Ediyanto Ediyanto (Universitas Muria Kudus, 2022)
The purpose of this research is to analyze the relationship between Lego games and the learning concentration of autistic children. The research method used is quantitative with correlational study techniques. This study uses data analysis and testing the Spearman Rank Correlation hypothesis. Collecting data using observation. The subjects in this study were autistic children. The results showed that there was a significant relationship between Lego games and the learning concentration of autistic children. This is shown by testing the hypothesis using the Spearman rank correlation coefficient formula with a value of 0.9 greater than the rho table value of 0.886 at an error level of 5%.